Regional Climate Drives Spatial Variation in Species Richness in the Most Diverse Family of Neotropical Snakes (Colubroidea: Dipsadidae) - Juan P. Ramírez; Julián A. Velasco; Tod W. Reeder (Ecology and Evolution)
ABSTRACT Species richness gradients are frequently associated with spatial variation of environmental conditions. However, understanding how the regional environment influences species assemblages is an ongoing topic of discussion, with three non‐exclusive explanations being proposed. Under these hypotheses, climate can determine the richness of regions in two main ways: (1) directly, by determining their carrying capacity, or (2) indirectly, through its effects on either (a) lineage diversification (i.e., the rates of speciation and/or extinction), or (b) the duration over which regions have been accumulating species. Recently, some studies have started to simultaneously evaluate and compare the role of these mechanisms in determining richness gradients. For this work, we set out to identify the factors that determine the spatial variation in richness of the hyperdiverse snake family Dipsadidae. To achieve this goal, we first calculated the number of species of the group in 100 × 100 km cells throughout its distribution. Then, using piecewise structural equations, we evaluated and compared the ability to predict the richness of these cells by several environmental (current climatic seasonality and past climatic stability) and evolutionary variables (speciation rates and time for speciation). We found that the richness gradient of Dipsadidae is directly explained by current seasonality and productivity, with a limited role of macroevolutionary processes. Therefore, our results support the idea that current climate has a primary role in determining the geographic patterns of the richness of the group, with the influence of diversification and time on regional diversity potentially obscured by the elevated levels of dispersal within the group. Such a possibility needs to be evaluated in future studies that explicitly assess the impact of dispersal on regional richness, both for the Dipsadidae and other groups where similar results have been reported.